Configuration of Physical and Mechanical Characteristics of Fly Ash and Bottom Ash Replacement in Self-compacting Concrete (SCC) - Hassan, Mohd Ikhmal Haqeem; Abdul Kadir, Aeslina; Sarani, Noor Amira; Abdo Al-Khadher, Sadeq Abdullah
Generally, fly ash (FA) and bottom ash (BA) are produced by the process of combustion in coal-fired power plants that considered as waste which includes heavy metals in its composition. Moreover, these metals are harmful to both the atmosphere and human health. Apparently, for these ashes, treatment methods are available, and one of them is the replacement of FA and BA as concrete materials. Therefore, the primary purposed of this paper was to investigate the properties and characteristics of self-compacted concrete (SCC) incorporated with fly ash and bottom ash. SCC was developed with different percentages of FA and BA as a replacement for cement and sand with ratios of 10, 20 and 30% respectively. The properties tested were slump flow and t500 test, sieve segregation, and J-ring test for physical characteristic. Next, density, compressive power, and water absorption were examined to determine its mechanical characteristic. The results revealed that both physical and mechanical characteristics with 20% of FA and BA in SCC were suitable to be defined as SCC. A comparable set of data in compressive strength were observed, and densities have been established as standard weight concrete. In conclusion, this research demonstrates that FA and BA material are possibly be used as a new material for concrete production.